Analisis Perbandingan Klausul Hardship dalam Hukum Kontrak Indonesia dan Malaysia - Junaidi Arif (Bulletin of Community Engagement, 2026)
This study aims to analyse and reformulate hardship clauses within the Indonesian business legal system as an effort to reconcile legal certainty and contractual justice. The main issue raised is the absence of explicit provisions regarding hardship in the Civil Code, which leads to the dominance of the principle of pacta sunt servanda and has the potential to cause injustice in situations involving fundamental changes in circumstances. This study employs a normative legal research method using legislative, conceptual, and comparative approaches, whilst drawing upon principles of international contract law such as the UNIDROIT Principles of International Commercial Contracts. The findings indicate that the concept of hardship in modern contract law functions as a corrective mechanism to maintain contractual balance through renegotiation and adaptation of the contract. From the perspective of Gustav Radbruch’s theory of the purpose of law, a reformulation of the hardship clause is necessary to integrate the values of legal certainty, justice, and utility in a proportionate manner. Such reformulation can be achieved through the normative recognition of hardship, the establishment of objective parameters for significant changes in circumstances, and the granting of authority to judges or arbitrators to adjust contracts as a last resort. Thus, the reformulation of hardship clauses not only strengthens the national contract law system but also enhances the law’s adaptability to the dynamics of the modern economy.